Driving and photo-regulation of myosin–actin motors at molecular and macroscopic levels by photo-responsive high energy molecules. Issue 42 (13th September 2017) - Menezes, Halley M.; Islam, Md. Jahirul; Takahashi, Masayuki; Tamaoki, Nobuyuki
Abstract : Azobenzene based non-nucleoside triphosphates, AzoTPs, drive and photo-regulate the myosin–actin motor function at both molecular and macroscopic levels. Abstract : We employed an azobenzene based non-nucleoside triphosphate, AzoTP, in a myosin–actin motile system and demonstrated its efficiency as an energy molecule to drive and photo-regulate the myosin–actin motile function at the macroscopic level along with an in vitro motility assay. The AzoTP in its trans state induced shortening of a glycerinated muscle fibre whilst a cis isomer had no significant effect. Direct photoirradiation of a cis -AzoTP infused muscle fibre induced shortening triggered by a locally photo-generated trans -AzoTP in the muscle fibre. Furthermore, we designed and synthesized three new derivatives of AzoTPs that served as substrates for myosin by driving and photo-regulating the myosin–actin motile function at the molecular as well as the macroscopic level with varied efficiencies.